Excitation function for the reaction 197 Au (d,p) 198 Au - Jorge Nassiff, Sonia; Quel, E.; Testoni, J. E.; Sandoval, E. (North Holland Publishing, 1966)
Fil: Jorge Nassiff, Sonia Comisión Nacional de Energía Atómica; Argentina